ANALISIS STRATEGI RECOVERY EKONOMI DESA BERBASIS INTERNET OF THINGS (IOT) PADA KELOMPOK PETANI KOPI DESA MOTUNG KABUPATEN TOBASA - Eka Pratiwi Septania Parapat; Richard Berlien (Politeknik Bisnis Indonesia, 2021)
Economic conditions in various parts of the world are currently unstable because the impact of the Covid-19 pandemic cannot be overcome. All sectors were heavily affected. This condition is also experienced specifically by rural communities in parts of Indonesia. Previous researchers have also conducted research related to village economic recovery. One of the results of their research is to take advantage of the potential of agriculture and strengthen MSMEs. The specific purpose of this study was to analyze the technology-based village recovery strategy in Motung Village. The urgency of this research is to formulate a strategy in the context of village economic recovery based on IOT (Internet of Things). The analytical technique used in this study is the Miles and Huberman approach, namely the analysis process begins with data reduction, data display, and data verification/conclusion. The results of this study say that the village economic revovery strategy is to empower the community, build infrastructure related to technology, improve the quality of coffee agricultural products, distribution and marketing of coffee agricultural products, support creative economies.